Impact of the methods of groundwater access on irrigation and crop yield in the North China Plain: Does climate matter?. Issue 4 (7th November 2016) - Zhang, Lijuan; Wang, Jinxia; Zhang, Guangsheng; Huang, Qiuqiong
Abstract : Purpose: The purpose of this paper is: to track the methods by which farmers access groundwater for irrigation in the North China Plain (NCP); to explore whether climate factors influence farmers' decisions on the methods of groundwater access for irrigation; and to examine whether the amount of groundwater use for irrigation and crop yield systematically differ across groups of farmers using various methods of groundwater access, and how climate factors affect them. Design/methodology/approach: Descriptive statistical analysis and econometric models are used on household survey data collected over several years and county-level climate data. Findings: Over the past few decades, a significant share of farmers have switched the methods of groundwater access from collective tubewells to own tubewells or groundwater markets. Farmers who bought water from groundwater markets applied less water to wheat plots than those who had their own tubewells. However, wheat yield was not negatively affected. Both average climate conditions and long-term variations were found to be related to farmers' choice of methods of groundwater access for irrigation. More frequent droughts and increasingly volatile temperatures both increased the likelihood of farmers gaining groundwater irrigation from markets. Originality/value: The analysis results suggest farmers are using groundwater markets to help them adapt to climate change. Applying empirical analysis to identify the impact of the methods by which farmers access groundwater for irrigation on the amount of groundwater use and crop yield will help policy makers design reasonable adaptation policies for the NCP.